Caregivers’ Grit Moderates the Relationship Between Children’s Executive Function and Aggression - Lam, Bess Y. H.; Raine, Adrian; Fung, Annis L. C.; Gao, Yu; Lee, Tatia M. C. (Frontiers in Psychology, 2020)
Objective: Previous studies have shown that the impairment of executive function is positively related to aggression in children and adolescents. What is worthwhile investigating is the moderator of such relationship so that aggressive behavior can be reduced effectively in those who have executive function problems. The present study examined the association between executive function and two major subtypes of aggression (proactive and reactive aggression) and whether their caregivers’ grit (perseverance) moderated such relationship. Method: Executive function and reactive and proactive aggression was assessed in 254 children and adolescents aged 8 to 19 years old, and their caregivers’ grit was measured. Results: Results show that caregivers’ grit plays a significant role in moderating the relationship between children’s executive function and proactive aggression after controlling for the covariates including the children’s age, gender, and family income. Specifically, children’s executive function became more negatively associated with proactive aggression when caregivers’ grit was high while the association was positive when it was low. On the other hand, the association between children’s executive function and reactive aggression did not vary across different levels of caregivers’ grit. Conclusions: These findings suggest that proactive aggression may be reduced in those who have better executive function by enhancing their caregivers’ grit which inform the design of interventions in adjunct with the current approach (e.g., executive function training) to reduce aggression in children and adolescents in the community.